Визначення умов наповнення гідравлічного компенсатора поршневого розчинонасоса - Вовченко, Володимир Петрович; Малюшицький, Олександр Володимирович; Васильєв, Євген Анатолійович; Васильєв, Анатолій Володимирович (НТУ "ХПІ", 2017)
Розглянуті умови забезпечення наповненості робочої камери гідрокомпенсатора розчинонасоса рідиною, яка одночасно є промивною для конструкції розчинонасоса з гідравлічним компенсатором пульсації тиску подачі розчинної суміші. Аналізуючи етапи роботи розчинонасоса, було встановлено, що на початку циклу нагнітання, у разі неповного заповнення робочої камери компенсатора рідиною, наприклад, через її витоки, в камері виникає розрядження. Це створює основу для пропозиції автоматичного наповнення і підтримки на необхідному рівні робочої рідини в камері компенсатора через зворотний клапан із завантажувальної місткості. Експериментальними дослідженнями підтверджена бездоганна працездатність запропонованої конструкції.

The article examines the terms of providing saturation of the working chamber in the hydraulic compensator of the mortar pump with the liquid, which is simultaneously washing liquid for construction of the mortar pump with hydraulic compensator of pressure pulsations of solution feeding. The circumstance that in the construction of the mortar pump there is a primitive unit, which lubricates the friction couple – the piston plunger and its cup-type seal, allows to increase its operational life notably, as this pointed out friction couple is the most vulnerable part of a mortar pump. In addition, the washing liquid at the same time functions as power liquid for working efficiency of a hydraulic compensator of the mortar pump. Therefore, potential consumption of the mentioned liquid in case of carrying out flushing functions should not have an adverse effect on general working efficiency of the mortar pump. After we had analyzed operational stages of the mortar pump, we elucidated that at the start of injection period, in case of incomplete admission (filling of working chamber of the pump compensator with liquid), for example, because of liquid leaks, there can occur depression in the working chamber. This is due to the fact that the amount of the mortar mix, which is pumped in delivery steps, will be unequal – smaller, that the amount of liquid, which is displaced by the compensator with supplementary air, which is stipulated by fluid loss. However, depression will not occur if the compensator is filled with air. It lays the foundation for suggesting autoinflation and support of power liquid at desired level in the pressure compensator cavity through the back-flow prevention valve from the charging tank. Impeccable working efficiency of the offered construction has been confirmed by experimental investigation. Except filling the pressure compensator cavity, this construction also affords to check to see the liquid filling level and the wear rate of a cup-type seal in a mortar pump.
Determining the conditions of filling the hydraulic compensator in a piston mortar pump
Keywords: диференціальний розчинонасос; промивна рідина; робоча камера; компенсатор; differential mortar pump; washing liquid; working chamber